Comparative Analysis of Text Complexity in English Textbooks - M. B. Kazachkova; Kh. N. Galimova (Дискурс профессиональной коммуникации, 2022)
The article presents the results of a comparative analysis of the complexity of texts on the material of the linguistic subcorpus of English textbooks “English”, “Starlight” and “Rainbow English” for the 11th grade. The total volume of the sub-corpus of texts acting as empirical material for the research amounted to 36 texts (3955 word uses). One of the characteristics of the complexity of the text is its readability. It depends on the degree of complexity of words and the structures used in the sentences, as well as on such quantitative parameters of the text as the average length of the sentence (in word usage) and the average length of the syllable in the word. The readability of the text is calculated with the help of the formulas of Flesh Reading Ease, Flesh-Kincaid Grade, and the Gunning Fog index known in linguistics. The results of the complexity assessment were obtained using the TextInspector automated text complexity analyzer program. It was revealed that the complexity of the texts in the textbooks under discussion corresponds to the age characteristics and intellectual level of high school students. At the same time, the complexity indicators of the texts in the textbook “Starlight” are higher than the indicators of the textbooks “Rainbow English” and “English”, which is explainable, since the textbook “Starlight” is intended for schools with in-depth study of the English language. The automatic analysis of the complexity of educational texts using information technologies based on methods of their